A REVIEW OF THE ECONOMIC IMPACT OF THE COVID-19 PANDEMIC ON THE AUTOMOBILE INDUSTRY IN MALAYSIA (Journal of Economics and Sustainability, 2022)
The COVID-19 pandemic has resulted in a disastrous impact on the production and sales of many industrial sectors. Voluminous past literature has shed light on the negative implications of the pandemic crisis on these sectors. However, this paper aims to draw light on the impact of the pandemic crisis on the automotive industry, one of the nation’s largest industries. A comprehensive review will be performed to demonstrate the significant implications of the COVID-19 pandemic on the automobile industry. In addition, an evaluation of the government’s measures to mitigate the negative impacts of COVID-19 on individuals and economic sectors is presented in this paper. An examination of the effectiveness of the government’s move in assisting the recovery of the industrial sector, specifically the automotive sector, is done through the evaluation of the sales volume data. Therefore, the implications of this study are to demonstrate the association between the effect of the pandemic crisis and the automotive sector’s production. Secondly, to provide a review of the government’s measures and to present its association with the sales volume in gauging the effectiveness of the measures adopted. The findings of this study presented robust evidence of the negative implications of the COVID-19 pandemic on automobile production and sales volume. Notably, the decline of sales and production units is more apparent during the period of the nation’s lockdown due to COVID-19. Besides, this study has made a noteworthy contribution by discussing the government’s policy measures implemented during this pandemic crisis.